Silent Invader: Probable Phreatobacter Oligotrophus Sepsis In A Preterm Neonate - Aliyyah Mohammad Khuzaini; Saarah Huurieyah Wan Rosli; Nadia Yazid; Adilah W Ab Rahim (Jaypee Brothers, 2025)
Indexed by ERA